TRANSLATION STRATEGIES AND ACCURACY OF CONNOTATIVE NOUN PHRASES IN “A SPACE FOR THE UNBOUND” - Dzaki Difa Al Hadiid; Eky Edel; Eri Ester Khairas (Politeknik Negeri Jakarta, 2025)
The research is focused on the noun phrases that contain connotation in the game A Space for the Unbound. This study aims to identify the structure, connotative value, chosen translation strategies, and semantic fidelity of these phrases to determine how well the English version maintains the intent of the Indonesian source. This type of research is descriptive qualitative. The research object comprises 71 connotation-rich noun phrases taken from Chapters 1–5 of the original script and their published English counterparts. Data were collected through three procedures: content analysis of the entire in-game script, unstructured interviews with native English players to probe perceived connotation, and a focus-group discussion with bilingual raters who scored accuracy using Nababan et al.’s (2012) instrument. The instruments used were a coding sheet, an interview guide, and an accuracy-rating form. Data were analysed through Spradley’s ethnographic sequence domain, taxonomy, componential, and cultural analysis supplemented by frequency counts. The results show a dominance of subordinative structures (70/71, 98.6 %), with the source text leaning positive in connotation and the target text mirroring this distribution with minor shifts. Transcreation is the leading strategy (52.1 %), followed by literal translation (45.1 %), while foreignization and domestication appear only marginally; overall accuracy is very high (mean = 2.97/3). In conclusion, creative audience-oriented strategies are essential for conveying the game’s emotional nuance, and systematic accuracy checks remain crucial to safeguard semantic fidelity.